Tinjauan Kualitas Pelayanan Di Bangsal At-Tin Ditinjau Dari Dimensi Mutu Di Rumah Sakit PKU Muhammadiyah Sukoharjo - Febby Hutama Putra Ennando; Hesty Latifa Noor; Agus Trijono (Pusat Riset dan Inovasi Nasional, 2024)
The quality of health services is the degree of perfection of health services that are in accordance with professional standards and service standards by using the potential resources available in the hospital. The purpose of this study was to determine the Quality of Service in At-Tin Ward Reviewed from Quality Dimensions at PKU Muhammadiyah Hospital Sukoharjo.This research method is qualitative, namely a research procedure that produces descriptive data to determine the Quality of Service in At-Tin Ward Reviewed from Quality Dimensions at PKU Muhammadiyah Hospital Sukoharjo. The population in this study were the Head of PMKP, Head of Inpatient Room, Nursing Officer, IPSRS Officer, CS Officer and patients. The variables used in this study are Service Quality, with three dimensions of tangible quality, reliability, responsiveness. conducted in July 2024 to August 2024. The research instruments include observation guidelines, interview guidelines, Data Collection, Data Reduction, Data Display, Conclusion Drawing.The results of the study show Physical Evidence (Tangible) on the aspect of cleanliness. The cleaning staff carries out their duties well, the Aspect of the Availability of Medical Equipment is considered to be in accordance with the standards set for type C hospitals, the aspect of the condition of the ward room can be said to be not good enough, Reliability of officers has sufficient knowledge regarding the procedures and procedures for serving patients, Responsiveness is good quality of service in terms of communication, speed of service, and friendliness of staff.The conclusion of this study is that the Cleanliness Aspect still needs to be improved, Availability of medical devices for respiratory aids needs to be improved, Room conditions in the adult ward still need to be improved, Accurate and Reliable Service Medical personnel in the adult Inpatient ward have shown good competence in carrying out their duties, but there is no clear SOP regarding service times.